Redesigning courses for online delivery design, interaction, media & evaluation - Parker, Robyn E. (Bingley, U.K. : Emerald, 2013)
This volume examines key considerations for effective online course redesign. Using a 4-phase approach, Redesigning Courses for Online Delivery informs thinking, inspires creativity, and structures decisions to drive the development of high quality online learning experiences. Both scholarly and practical, it provides a comprehensive approach to redesign useful to novices and veterans alike.
Course redesign using the DIME model / Robyn E. Parker -- Metaphor as a frame for course redesign / Robyn E. Parker -- Design considerations / Robyn Parker -- Interaction considerations / Robyn E. Parker -- Media considerations / Robyn E. Parker -- Evaluation considerations / Robyn E. Parker -- Reprise and further considerations / Robyn E. Parker.
Print version record
Keywords: Education -- Computers & Technology; Education -- Higher; Education -- General; Educational equipment & technology, computer-aided learning (CAL); Colleges of higher education; Education, Higher -- Computer-assisted instruction; Web-based instruction; Instructional systems -- Design; Educational technology